2020
DOI: 10.3390/ma13051042
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Recrystallization Behavior and Processing Map of the 6082 Aluminum Alloy

Abstract: Multiple hot-compression tests were carried out on the 6082 aluminum (Al) alloy using a Gleeble-1500 thermal simulation testing machine. Data on flow stresses of the 6082 Al alloy at deformation temperatures of 623 to 773 K and strain rates from 0.01 to 5 s−1 were attained. Utilizing electron backscatter diffraction (EBSD) and a transmission electron microscope (TEM), the dynamic recrystallization behaviors of the 6082 Al alloy during hot compression in isothermal conditions were explored. With the test data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Aluminum alloy is a kind of high-stacking fault energy material, dynamic recovery and dynamic recrystallization is a common phenomenon. Hu et al [15] compressed the 6082 alloys at 350-500 • C and 0.01-5 s −1 , a substantial of subgrain boundaries were found after deformation. Li et al [16] conducted compression tests of 6082 alloy at elevated temperatures, they observed that the dislocations took a great change and different evolution under various conditions, which directly affects the mechanical properties of 6082 alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum alloy is a kind of high-stacking fault energy material, dynamic recovery and dynamic recrystallization is a common phenomenon. Hu et al [15] compressed the 6082 alloys at 350-500 • C and 0.01-5 s −1 , a substantial of subgrain boundaries were found after deformation. Li et al [16] conducted compression tests of 6082 alloy at elevated temperatures, they observed that the dislocations took a great change and different evolution under various conditions, which directly affects the mechanical properties of 6082 alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Newly developed grains also have LAGB in general, which in combination with previous results corresponds to the influence of combined effect of dynamic recovery and dynamic softening. During the first phase of dynamic softening, the dislocation density is increasing and material undergoes simultaneously a period of softening and hardening which results in the development of subgrains [6,7]. After achieving the deformation limit the dynamic balance occur.…”
Section: Resultsmentioning
confidence: 99%
“…After achieving the deformation limit the dynamic balance occur. Dislocation density is constant and subgrains are equiaxed, of the same size and the same orientation [6,7]. The main characteristic of dynamic recovery is the fact that microstructural changes are proceeding evenly throughout the whole volume.…”
Section: Resultsmentioning
confidence: 99%
“…High energy storage will drive original grain boundary migration to the regions with higher dislocation density, resulting in grain boundary bulging which has been proved by other researchers. [42,43] It can be seen from Figure 9e that subgrains exist within bulging grain boundaries, and the newly formed nuclei will generate and grow by continuous absorption of dislocations as well as grain boundary migration, which is the typical feature of DDRX. Further increasing the temperature to 500 °C, subgrain boundary disappearance appears (Figure 9f ) and the annihilation of the subgrain boundary implies subgrains merging to produce recrystallized grains with HABs.…”
Section: Relationship Between Shear Bands and Dynamic Recrystallizationmentioning
confidence: 99%